Penerapan Model Problem Based Learning (PBL) dalam Membentuk Kemampuan Berpikir Kritis Siswa SD Talenta Al-Fatih Saimbang Sidoarjo (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to identify and analyze students' critical reasoning skills in the Natural Sciences lesson of Talenta Al-Fatih Sidoarjo elementary school. This research focuses on the use of problem-based learning models to improve students' critical thinking skills in the study of Natural Sciences. This study uses a qualitative method through a naturalistic approach. Data collection uses observation, interviews, and documentation. Data analysis techniques use reduction, presentation, and conclusion drawing techniques. The results of the analysis found that the critical reasoning skills of SD Talenta Al-Fatih Sidoarjo students in science lessons can be known from the indicators of being able to formulate the main problem in a material, being able to answer questions in the main problem, being able to solve problems, and being able to make conclusions. The Problem-Based Learning Model (PBL) to improve students' critical reasoning skills at SD Talenta Al-Fatih Sidoarjo in Natural Sciences lessons is carried out with its activity program Supporting factors and hindering the application of the problem-based learning model to improve students' critical reasoning skills in learning Natural knowledge is a supporting factor including students, principals, and teachers and an ineffective learning process and limited time is an obstacle